A IMPORTÂNCIA DA FISIOTERAPIA NA MELHOR IDADE (PRÁXIS EM SAÚDE, 2024)
While we disagree about the future of human beings, data indicates that by 2030 Brazil will have the fifth oldest population in the world. The natural aging process results in the loss of muscle mass and other dysfunctions, which result in greater functionality of the system. Therefore, physiotherapy plays a fundamental role in maintaining life, and it is necessary to reinforce information about the importance of physiotherapeutic monitoring and that of other professionals, who work with the intention of providing elderly people with a more comfortable and safe life when carrying out daily activities. This research aims to identify and compile results that identify the main pathologies affected in older age, as well as the work of professional physiotherapists in generating benefits and improving the condition of patients. The results to be presented were prepared using scientific methodology based on bibliographic investigations, articles, books and also descriptive field research. We can observe and conclude that physiotherapy at an older age is essential and extremely important for functional and motor maintenance, reversing or alleviating the issues addressed, thus maintaining the quality of life of these elderly people.
Keywords: Elderly; Physiotherapy; Pathologies